The international law of energy / Jorge E. Viñuales, University of Cambridge. - Viñuales, Jorge E. (Cambridge studies in international and comparative law ;, 2022)
The world's energy structure underpins the global environmental crisis and changing it will require regulatory change at a massive level. Energy is highly regulated in international law, but the field has never been comprehensively mapped. The legal sources on which the governance of energy is based are plentiful but they are scattered across a vast legal expanse. This book is the first single-authored study of the international law of energy as a whole. Written by a world-leading expert, it provides a comprehensive account of the international law of energy and analyses the implications of the ongoing energy transformation for international law. The study combines conceptual and doctrinal analysis of all the main rules, processes and institutions to consider the past, present and likely future of global energy governance. Providing a solid foundation for teaching, research and practice, this book addresses both the theory and real-world policy dimension of the international law of energy.